2016
DOI: 10.1007/s00421-016-3330-1
|View full text |Cite
|
Sign up to set email alerts
|

Muscle focal vibration in healthy subjects: evaluation of the effects on upper limb motor performance measured using a robotic device

Abstract: The results of our study support the use of focal muscle vibration protocols in healthy subjects, to improve motor performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…Two studies were added, resulting from the chain searching. Consequently, a total of 12 eligible studies were included in the present review [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. The study selection flow chart is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were added, resulting from the chain searching. Consequently, a total of 12 eligible studies were included in the present review [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. The study selection flow chart is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Murillo et al observed a decrease in limb spasticity irrespective to the lesion being motor complete or incomplete after muscle FV [15]. This finding is important to assure that the type and the level of injury doesn't necessarily need to be regarded for the application of FV therapy, especially when our proposition to use FV coupled with robotic assisted therapy could advance the outcomes in movement therapy even after spasticity is diminished [16], [12]. Our study when completed, will also compare each treatment (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Measure Active Range of Motion (AROM) 12 Measure Passive Range of Motion (PROM) 13 Measure Joint Stiffness (JS) 14 Play a PONG game 15…”
Section: B Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps there is no cortical involvement in the response to vibro-tactile stimulation. While recent evidence points towards the use of focal vibro-tactile stimulation to precondition the muscle to increase its force, there is still the question as to which mechanism is responsible for this effect [13], [29].…”
Section: A Focal Vibrations Eeg Experimentsmentioning
confidence: 99%